2020
DOI: 10.5539/ies.v13n4p17
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Students in Thailand on the Use of Humor in University Classroom

Abstract: Humor is a serious business. This study explores the perception of students in Thailand on the use of humor in business classrooms indicating that humorous classroom brings about physiological and emotional benefits to students as it relieves tension and stress, makes the classroom atmosphere more comfortable and less intimidating, and facilitates better teacher-student relationship. Around 358 students from a business school in Thailand were surveyed and the results found that most of the students prefer to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…The statement made by Daffa confirms the figure (3) and chart (2), which indicates that the vast majority of learners are at content with a method of learning that incorporates comedy elements into the content they are being taught. In line with this, humour undoubtedly creates a positive emotional atmosphere, fostering happiness and relaxation, which in turn reduces students' stress and anxiety (Sterling & Loewen, 2015).…”
Section: Excerpt 2 (In-depth Interview)mentioning
confidence: 56%
“…The statement made by Daffa confirms the figure (3) and chart (2), which indicates that the vast majority of learners are at content with a method of learning that incorporates comedy elements into the content they are being taught. In line with this, humour undoubtedly creates a positive emotional atmosphere, fostering happiness and relaxation, which in turn reduces students' stress and anxiety (Sterling & Loewen, 2015).…”
Section: Excerpt 2 (In-depth Interview)mentioning
confidence: 56%
“…Selera humor yang dimiliki oleh seseorang dapat membuat suasana belajar peserta didik menjadi lebih kondusif dan menyenangkan (Embalzado & Sajampun, 2020). Dengan catatan humor yang dilakukan oleh guru tidak berlebihan dan tetap dengan konsep pembelajaran yang baik (Park et.…”
Section: Pendahuluanunclassified
“…Notably, Bieg et al (2019) reported in their study that only course-related humor was effective, and teachers should avoid aggressive humor. More recently, Embalzado and Sajampun (2020) identified that most of the Thai students prefer to have a certain degree of humor in the university classroom. In this sense, it is likely to assert that humor may be a useful pedagogical tool in classrooms.…”
Section: Introductionmentioning
confidence: 99%